Úprava systému řízení vozu Formula Student pro schopnost autonomní jízdy. - Novotný, Jindřich; Jindřich Novotný (České vysoké učení technické v Praze, 2023)
Práce se zabývá mechanickou stránkou úpravy systému řízení vozu Formula Student pro tým eForce FEE Prague Formula. Část práce se zabývá popisem problému a následně změřením sil v řízení za účelem dimenzování komponent. Podle těchto požadavků je následně zvolen celkový koncept úpravy systému a je vyhodnocena nutnost úprav stávajících komponent a design nových. Jsou také vyhodnoceny potřebné parametry kupovaných součástí a díly vhodně zvoleny. Na závěr je popsán způsob montáže systému a integrace do monopostu FSE.12.

The thesis deals with the mechanical adaptation of the steering system of a Formula Student vehicle for the eForce FEE Prague Formula team. A part of the thesis describes the problem, followed by the measurement of steering forces for the sake of dimensioning the compoments. The overall concept of the adaptation is chosen with respect to these requirements, and necessary changes to existing components are evaluated and new ones are designed. Parts to be bought are then assessed with regard to the required parameters and suitably chosen. The thesis then describes the assembly process of the system and integration into the FSE.12 formula.
Adaptation of a Formula Student steering system for autonomous driving capability.
Keywords: Řízení; eForce; Formula Student; Autonomní jízda; Steering; eForce; Formula Student; Autonomous driving